(untitled) (Tazakka: Jurnal Pendidikan dan Keislaman, 2025)
Learning Islamic Religious Education (PAI) for first grade elementary school students requires an interesting and effective approach to improve memory. Song media is one promising alternative because it is in accordance with the characteristics of students who like to play and sing. This study aims to describe the application of song media in learning Islamic Religious Education (PAI) to improve the memory of first grade students at SD Negeri 28 Air Tawar Timur, and to identify supporting and inhibiting factors. This study uses a qualitative descriptive method. Data were collected through observation, interviews, and documentation. The results showed that the use of song media was effective in improving students’ memory of PAI material. Students showed high enthusiasm and were able to remember the material better when presented in the form of songs. Supporting factors include students’ interest in songs, teacher creativity in creating songs, and support from the school. Inhibiting factors include time constraints, inadequate facilities and infrastructure, and differences in student learning styles. The use of song media can be an effective learning strategy in improving the memory of first grade students in PAI subjects. However, attention needs to be paid to inhibiting factors so that the implementation of song media can run optimally. This study provides important implications for the development of more innovative and enjoyable PAI learning methods.